Tom Scheerer decorates - Read, Mimi (Vendome Press, 2013)
"From Park Avenue apartments to Maine country houses to Bahamian seaside cottages, leading interior designer Tom Scheerer creates rooms that are crisp, confident, and visually enthralling. He combines classic, old-fashioned decorating with modernist touches, simple, natural materials, beckoning palettes, and vernacular crafts. The result, as seen on every page of this first book of his work, is an object lesson in highly sophisticated, yet relaxed, unpretentious decor."--